Analisis Pengaruh Disiplin Kerja Beban Kerja Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Dinas Perhubungan Kabupaten Alor - Duka, Adriana Th.; Peny, Theresia Lounggina Luisa; Hermayanti, Hermayanti; Gorang, Alvonso Fanisius (Jurnal Ilmiah Wahana Pendidikan, 2023)
Employee performance is the work performance achieved by an employee, namely the comparison between work results and the standards set at the Alor District Transportation Office. The purpose of this study was to determine the effect of work discipline, workload, work environment and organizational culture on employee performance at the Alor District Transportation Office. This type of research is a quantitative description. Samples were taken using saturated sampling technique. The sample in this study were 48 employees. Data collection tools used are observation, interviews, and literature studies. The data analysis model used to answer the hypothesis is multiple analysis, t test, F test. This research instrument test is used to measure the level of validity, reliability and classic assumptions from the answers to the research questionnaire. By using the tool to calculate SPSS version 22 For Windows. Based on the results of the validity test for each variable with a Pearson correlation value ≥ 0.3, the results of the validity test for each variable are declared valid. The reliability test results for each variable with a Crobatc Alpha value ≥ 0.6, the reliability test results for each variable are declared reliable. Shapiro-Wilk Normality test results with sig. ≥ 0.05 then the test results are declared normal. The results of the heteroscedasticity test showed that the value of each independent variable was > 0.05, so there was no heteroscedasticity in this study. The results of the multicollinearity test show that the VIF value > tolerance means that multicollinearity does not occur in this study. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity value is > 0.05, so there is a relationship between the dependent variable and the independent variable.The analytical method used is multiple linear regression analysis technique. The results with the t test to answer the first, second, and third hypotheses, while multiple linear regression analysis simultaneously used the F test to find out the fourth hypothesis, namely to determine the effect of work discipline, workload, work environment and organizational culture on employee performance at service offices Alor Regency Transportation. Based on the results of multiple linear regression analysis calculations partially and simultaneously, the significance value of the work discipline variable is 0.020, the workload variable is 0.019, the work environment variable is 0.011, the organizational culture variable is 0.042, and the simultaneous effect of the significance value of the F test is 0.000b, the results of the t test and F test are smaller than alpha (0.05), so the hypothesis testing proposed in this study is as follows: there is an influence of work discipline, workload, work environment and organizational culture on employee performance at Alor District Transportation Office.